Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/02688697.2016.1206181
|View full text |Cite|
|
Sign up to set email alerts
|

Neurogenic claudication secondary to degenerative spondylolisthesis: is fusion always necessary?

Abstract: A primary decompression using a midline sparing osteotomy is an effective procedure for the treatment of neurogenic claudication caused by DS. The second message is that on inspection of the pre-operative imaging, sagittally placed facet joints, a hyperlordosis and a preserved disc height then a fusion procedure should be considered primarily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…In contrast to previously published studies, 3,16 our analysis did not show any correlation between disc height and instability. We speculate that the small number of patients in our study or the different assessment tool (MRI vs radiography) may explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previously published studies, 3,16 our analysis did not show any correlation between disc height and instability. We speculate that the small number of patients in our study or the different assessment tool (MRI vs radiography) may explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, three recent non-comparative cohort studies have also demonstrated safety and efficacy of spinal decompression in populations with low-grade spondylolisthesis with spinal stenosis [19][20][21]. In these studies at long-term follow-up, patients had improvements in ODI, EuroQol Five Dimensions (EQ-5D), or visual analogue scale (VAS) for back and leg pain scores.…”
Section: Surgical Decompressionmentioning
confidence: 98%
“…The eligible cases were those (6) patients who had DLS and received surgical treatment in the period of 2003-2013 at the Neurosurgical Division, Surgery Department, Faculty of Medicine of Ramathibodi Hospital. Surgery was carried out on those patients who were suffering from back pain, radicular pain, or neurological claudication even after 3 months of conservative management (18). A total of 25 men and 75 women having an average age of 61 years were recruited.…”
Section: Subjectsmentioning
confidence: 99%
“…It seldom occurs before the age of 50 years and is approximately four times more prevalent in women than in men (15). Its features include spinal stenosis with an anterior translation not exceeding 30% of the width of the vertebral body (18). DLS patients may suffer from back and leg pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation